Space suitability and its functional implications in interior design (Al-Academy, 2023)
The current research dealt with the study of space compatibility and its role in enhancing the functional aspect of the design of the interior spaces of isolation hospitals by finding a system or format that is compatible with the nature of the changes occurring in the structure and function of the space system, as well as contributing to enhancing compatibility between the functional aspect and the interior space. Therefore, the designer must The interior is the study of the functional and spatial aspects as they are the basic aspects for achieving suitability, and through the interaction between the person and the place, the utilitarian performance characteristics are generated that the interior designer is interested in and tries to develop and give them the appropriate design fit. The research consists of four chapters:* The first chapter: dealt with the research problem that was crystallized by the following question: “What is the role of spatial suitability in the process of change to embody the functional aspect of interior design?” The importance of the research is demonstrated by presenting a study necessitated by the necessity of raising the level of interior spaces, especially with regard to the issue of space suitability. The research also contributed to benefiting researchers and students regarding the results reached by the current research in the field of space suitability and confirming the functional aspect of interior design. The aim of the research is to clarify the role of adapting the interior space to the nature of the changes occurring in its systems and to confirm the functional aspect for which the space was designed. The first chapter also included the limits of the research (the objective limit, the spatial limit, the temporal limit) and the definition of terminology. The second chapter included the theoretical framework, which was divided into two sections, the first of which was: suitability, its concept, and its types. The second section was: the spatial organization of patient residence wards in hospitals